Pengaruh Lamanya Pengobatan Terhadap Profil Darah pada Penderita Tuberkulosis Paru di Puskesmas Oesapa - Ni Made Susilawati; Novian Agni Yudhaswara; Karol Octrisdey (Jurnal Ventilator, 2023)
Control efforts with the DOTS (Directly Observed Treatment Short-course) strategy have been implemented. The side effects of this drug will continue as long as the sufferer takes it, furthermore anti-TB drugs (OAT) will change the metabolism in the sufferer's body. Chronic effects that arise from OAT treatment include increased levels of uric acid, glucose and hemoglobin in the blood. From the results of a preliminary study, data collection was carried out on the number of pulmonary TB sufferers in Kupang City in 2021, amounting to 385. Of this number, 72 cases were found at the Oesapa Community Health Center who were smear positive for pulmonary TB and had recovered and were still undergoing treatment. For this reason, it is necessary to carry out research to determine blood glucose, uric acid and hemoglobin levels in pulmonary tuberculosis (TB) patients who take OAT (anti-TB drugs) before taking, after taking 2 months and 6 months of treatment. This research method is descriptive and statistical. Statistical analysis using One Way Anova and Linear Regression tests was used to determine the effect of length of treatment on blood profiles in pulmonary tuberculosis sufferers. TB sufferers with anti-tuberculosis drug therapy at the Oesapa Community Health Center based on the age of the patient, there were 11 sufferers aged <30 years (55%), 9 sufferers aged >30 years (45%). Based on gender, 13 sufferers were female (65%), 7 sufferers were male (35%). Hemoglobin levels checked before treatment showed a mean of 13.015 g/dL, during 2 months of treatment 13.185 g/dL, and after 6 months of treatment the mean was 11.94 g/dL. The current blood sugar levels from table 1.3 above which were checked before treatment showed an average of 137.7 g/dL, during 2 months of treatment 145.15 g/dL, and after 6 months of treatment the average was 144.15 g/dL. Uric acid levels were based on the respondent's length of treatment with an average uric acid level before treatment of 6.16 mg/dL, 2 months of treatment 5.92 mg/dL and 6 months of treatment 6.43 mg/dL. Hemoglobin levels, instant blood sugar and uric acid before, 2 months and 6 months of treatment showed a p value <0.05, meaning the data was not normally distributed. The results of the analysis using the Friedman anova test showed a p value (0.137) > 0.05. This means there is no difference in uric acid measurement values ??before, 2 months and 6 months of treatment. The results of the analysis using the Friedman anova test showed a p value (0.142) > 0.05. This means that there is no difference in blood sugar measurement values ??before, 2 months and 6 months of treatment. The results of the analysis using the Friedman anova test showed a p value (0.378) > 0.05. This means there is no difference in Hb measurement values ??before, 2 months and 6 months of treatment